CD62Ldim Neutrophils Specifically Migrate to the Lung and Participate in the Formation of the Pre-Metastatic Niche of Breast Cancer - Wang, Zhen; Yang, Chenghui; Li, Lili; Zhang, Zhigang; Pan, Jun; Su, Ke; Chen, Wuzhen; Li, Jinfan; Qiu, Fuming; Huang, Jian (Frontiers in Oncology, 2020)
Breast cancer is the most common malignant tumor in women, and lung metastasis is one of the leading causes of death in breast cancer patients. The mechanism of tumor metastasis is still controversial at present. Recently, the formation of pre-metastatic niche is considered to be a key factor for breast cancer metastasis, which could also explain the tendency of organ metastasis. Our study firstly re-explored the critical time of the niche formation, and simultaneously found a group of CD62Ldim neutrophils subsets that were not reported previously in tumor, which progressively increased during breast cancer progression and lung metastasis, and was closely related to the pre-metastatic niche formation. Furthermore, we explored the mechanism of their aggregation in lung pre-metastatic niche and found that they were specifically chemoattracted through the CXCL12-CXCR4 signaling pathway, and also has stronger adhesion capabilities and survivability. The results will provide new ideas for subsequent targeted treatment.